Cellular activation of selected signaling proteins through resistance training—a training methodological perspective - Nitzsche, N.; Neuendorf, T.; Gehlert, S.; Fröhlich, M.; Schulz, H. (German Journal of Exercise and Sport Research, 2018)
The Akt-mTOR-p70S6k-4E-BP1 signaling pathway is a well-considered regulator of protein synthesis in the context of strength training. This process is essential for exercise-induced skeletal muscle growth. The objective of this review article was to analyze the design of acute resistance training protocols and evaluate the possible impact of different loading conditions on the activation of growth-related signaling cascades in human skeletal muscle. In all, 12 human studies were included in this review. The training intensity in the studies varied between 30% 1RM (one repetition maximum) and maximal load. The signaling proteins were measured in a time range between immediately and 24 h after training. The phosphorylation of all signaling proteins increased to different levels after resistance training, tending to baseline more than 6 h post training. In particular, the hypertrophic associated p70S6k showed the highest phosphorylation acutely after the load and decreased consistently after 6?h. Training intensity and volume seemed to have an influence on the extent of protein phosphorylation, which, however, was not systematic or consistent. An obvious training methodological consequence (load and volume) for hypertrophic resistance training regime could not be devised. Further research is required to systematically vary training parameters to determine the influence of a certain stress zone on the signaling activation. Future research should aim to identify the ideal level of training intensity necessary to achieve the greatest possible extent of intramuscular anabolic signaling through intense activation of the signaling cascade to induce growth in human skeletal muscle.